Sesbania and lablab supplementation of oat hay basal diet fed to sheep with or without maize grain - Nsahlai, I.V.; Umunna, N.N. (Elsevier, 1996)
This study investigated the effects of supplementing oat hay (OH; milk stage at harvest) with 250 g(as-fed) of either lablab (Dolichos lablab, 50 percent flowering at harvest) hay or sun dried leaves of sesbania (Sesbania sesban) with or without 91 g dry matter (DM) of crushed maize grain on rumen pH and ammonia concentration (RAC), intake, degradability, rumen particle passage rate (kl) (in Experiment 1), digestibility, microbial N synthesis and live weight gain (LWG) (in Experiment 2). A randomized complete block design with a 2 X 2 factorial structure was used in both experiments. In sacco DM and N degradabilities of the feeds were also determined in three sheeSesbania degraded faster and to a greater extent than lablab DM. Lablab N was more soluble than sesbania N. Maize-free diets of sesbania and lablab had similar k1 but k1 was lower (P<0.05) for lablab than for sesbania in the presence of maize. No other effect of forage legume by maize grain interaction was significant. Crushed maize grain induced lower (P<0.05) pH, tended to depress the rate of OH degradation by 23 percent, depressed (P<0.05) hay intake, increased the intake of DM (P<0.05) and N (P<0.001) and the growth rate of sheep (P<0.05) but had no effect on the digestibility (DM, OM, neutral detergent fibre (NDF) or N) and microbial N synthesis. Multiple regression analysis indicated pH (P<0.03) but not RAC (P>0.05) affected the rate of OH degradation. Sesbania sustained higher (P<0.001) RAC, lower (P<0.05) potential degradability of OH and higher intakes (P<0.01; OH, DM and N), N digestibility (P<0.05), N retention (P<0.01) and microbial N synthesis (P<0.07) than lablab. Sesbania and lablab diets had similar rates of OH degradation, digestibility (DM, OM or NDF) and LWG. It was concluded that sesbania promoted higher OH intake and tended to increase (P<0.08) microbial N supply but had no effect on LWG. Maize grain tended to depress OH degradation rate but promoted faster LWG.